Quality Control Using the Six Sigma Method to Minimize Damage to Type 2268.2 Jars at PT X - Charismanda Adilla Tristanto; Muhammad Sufyan Tsaury; Raiza Ika Febriana (Universitas Muhammadiyah Lamongan, 2026)
PT X is a plastic jar manufacturing company that produces 14,000 jars per day using 12 machines. A recurring problem is the high number of defective products, which makes lid-to-body assembly difficult. This study aimed to identify the causes of defects and recommend quality improvements using the Six Sigma method. The results showed that the most frequent defects were falling breakage (1,004 cases) and ejection defects (712 cases). Statistical control values (CL, UCL, and LCL) were still within control limits, while the cause-and-effect analysis indicated that human factors were the main source of defects. The key improvement priorities are strengthening SOP implementation and providing better training on injection machine operation. Although the sigma level of 4.1 indicates fairly good performance, quality improvement remains necessary to enhance productivity.